2013
DOI: 10.1002/art.37885
|View full text |Cite
|
Sign up to set email alerts
|

Variants in RUNX3 Contribute to Susceptibility to Psoriatic Arthritis, Exhibiting Further Common Ground With Ankylosing Spondylitis

Abstract: Objective. Psoriatic arthritis (PsA) is a common inflammatory joint disease distinct from other chronic arthritides and frequently accompanied by psoriasis vulgaris. In a first genome-wide association study (GWAS), we were able to identify several genetic risk factors. However, even combined with previously identified factors, the genetic contribution to disease was not fully explained. Therefore, we undertook this study to investigate further 17 loci from our GWAS that did not reach genome-wide significance l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 24 publications
3
44
0
1
Order By: Relevance
“…For example, deletion of the The SNP rs10903122 near RUNX3 associated with celiac disease is also associated with atopic dermatitis [133] and the SNP rs4649038 in RUNX3 intron-1 is associated with psoriatic arthritis [134]. c The SNP rs7551188 in RUNX3 intron-1 gave a strong association signal with CD in a Japanese population, but it did not reach the required GWAS significant level [54].…”
Section: Skin Tumorsmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, deletion of the The SNP rs10903122 near RUNX3 associated with celiac disease is also associated with atopic dermatitis [133] and the SNP rs4649038 in RUNX3 intron-1 is associated with psoriatic arthritis [134]. c The SNP rs7551188 in RUNX3 intron-1 gave a strong association signal with CD in a Japanese population, but it did not reach the required GWAS significant level [54].…”
Section: Skin Tumorsmentioning
confidence: 98%
“…2). Other relevant examples include the association of SNP rs10903122, located near RUNX3, with both celiac disease [130] and atopic dermatitis [133]; rs4649038 in RUNX3 intron 1 with psoriatic arthritis [134]; and rs11580498, located 13 kb downstream of RUNX3, with asthma in a Canadian population [135] ( Table 5 and Fig. 2).…”
Section: Skin Tumorsmentioning
confidence: 99%
“…Concerning the environmental risk factors, it is important to mention: stress, low-humidity, drugs, smoking, obesity and chronic infections. In addition, numerous susceptibility genes and variants (LCE3B, LCE3C, TRAF3IP2, polymorphisms in IL-17, IL-23, RUNX3 and TNF*-857) have been recognized as contributing risk factors for PsA [15,[18][19][20][21][22][23][24]. Concerning the treatment of PsA, the available therapeutic approaches are mainly oriented to relief the inflammation and/or the associated-symptoms and to 'slow-down' the progression to more advanced and severe stages of the disease.…”
Section: Pharmacogenomics and Psoriatic Arthritismentioning
confidence: 98%
“…It has been identified that the RUNX3 polymorphisms were associated with susceptibility to ankylosing spondylitis in western European and Chinese Han population [5]. RUNX3 could influence the severity of ankylosing spondylitis by affecting the inflammatory process.…”
Section: And A4)mentioning
confidence: 99%
“…It is considered that autoimmune diseases might share common pathogenesis and susceptibility genes. Recently, RUNX3 has been investigated in other autoimmune diseases, such as Crohn's disease [3], celiac disease [4], psoriatic arthritis and ankylosing spondylitis [5]. To explore the role of RUNX3 in the pathogenesis of SLE, We genotyped 3 SNPs (rs7536201, rs4649038, rs11249215) identified from 2 previous studies [5,6] and analyzed the correlation between them and SLE subphenotypes in Han Chinese population.…”
mentioning
confidence: 99%